Driving Performance Through Discipline Loyalty and Motivation in Indonesia (Mendorong Kinerja Melalui Kedisiplinan, Loyalitas dan Motivasi di Indonesia) - Amalia, Adinda Putri; Firdaus, Vera (Indonesian Journal Publisher, 2024)
This research investigates the collective impact of work discipline, loyalty, and motivation on employee performance, addressing a significant gap in understanding the synergistic effects of these factors in an industrial setting in Indonesia. Utilizing a quantitative methodology, the study tested hypotheses through multiple linear regression analysis, including t-tests, F-tests, and determination coefficients, with SPSS software. A sample of 100 employees was surveyed using a structured questionnaire. Results indicated that individually, work discipline, loyalty, and motivation significantly enhance performance. Collectively, these factors synergistically improve employee outcomes, suggesting that integrated approaches to managing workforce dynamics can substantially benefit organizational efficiency. These findings underscore the importance of fostering a disciplined, loyal, and motivated workforce to boost performance in industrial sectors.